Sikap Anak Terhadap Pola Asuh di Panti Asuhan Pelangi Kasih Medan Helvetia - Hikmah, Yona Mulia; Atika, Tuti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the attitudes of children towards parenting practices at the Pelangi Kasih Orphanage in Medan Helvetia. Children, as a trust and gift from Allah SWT, require care that addresses physical, psychological, social, cognitive, and spiritual aspects. As primary caregivers, parents or care institutions play a crucial role in creating a loving and secure environment for children. This research uses a descriptive qualitative method to depict the children's attitudes towards the parenting practices implemented at the orphanage. Data collection instruments in the form of questionnaires or surveys are used to describe children's attitudes towards regulations, coaching, and relationships between leaders, caregivers, and foster children. The collected data will be analyzed descriptively, by calculating the frequency of answers or measuring the intensity of children's attitudes (positive, neutral, or negative).Attitudes towards guidance were divided between agreement and disagreement, while the relationship between the leadership, caregivers, and children was predominantly marked by dissatisfaction. These findings suggest the need for evaluation and improvement in communication, interaction, and the quality of guidance at the orphanage. The study recommends a more flexible and responsive approach in implementing parenting practices, with a focus on adjusting programs to better meet the needs of the children at Pelangi Kasih Orphanage in Medan Helvetia